The progress of immunotherapy for glioblastoma - Zhou, Qiangyi (Hum Vaccin Immunother, 2015)
Glioblastoma is the most common primary brain tumor in adults, accounting for about half of all primary brain tumors. Despite multiple therapeutic interventions such as surgical resection, radiotherapy, and systemic chemotherapy, the prognosis for glioblastoma remains poor. Due to the scientific community's enhanced understanding of the CNS immune system and significant achievements in tumor immunotherapy in recent years, immunotherapy has become a promising GBM treatment. In vaccine therapy, a number of clinical trials have achieved encouraging results. In antibody therapy, antibodies are used to target immune checkpoints such as ipilimumab and nivolumab. Bioengineering technology has also lead to a new field of tumor immunotherapy, whereby genetically modified tumor-specific T cells are reintroduced into a patient's body.